"All‐Water" Synthesis of β‐Amino α, α‐Difluoro Ketones from Fluorinated Enol Silyl Ethers and Imines. Issue 24 (26th June 2017) - Wu, Ye‐bin; Wan, Li; Lu, Guo‐ping; Cai, Chun
Abstract : A one‐pot synthesis of β‐amino α, α‐difluoro ketones without any additives was developed. Through a series of control experiments we found that water played a crucial and indispensable role. The hydrogen bond between water and fluorinated enol silyl ether had a significant impact on the addition reaction. Abstract : A one‐pot synthesis of β‐amino α, α‐difluoro ketones without any additives is developed. Through a series of control experiments we find that water plays a crucial and indispensable role. A hydrogen bond between water and the fluorinated enol silyl ether has a significant impact on the addition reaction.